Impacts of pandemic COVID-19 on dental urgencies in Primary Health Care: an ecological study - Gondim, Raquel Silva; Melo, Laila Melo de; Vieira, Ed Wilson Rodrigues; Rocha, Najara Barbosa da (ABCS Health Sciences, 2023)
Introduction: After the onset of the Covid-19 pandemic, oral health care in Primary Health Care (PHC) services in Brazil focused on emergency care. Objective: To evaluate the impact of the Covid-19 pandemic on the number of emergency dental visits in PHC in Brazil. Methods: This was an analytical and ecological study with data from the Health Information System for Primary Care referring to the number of attendances performed from March to December 2018 to 2020 in PHC services throughout Brazil for toothache, abscess, and dentoalveolar trauma. Differences between the monthly medians of the number of attendances before the pandemic (April to December 2018 and 2019) and during (April to December 2020) were analyzed using the independent-samples Mann-Whitney U test considering the interquartile ranges (IQR). Results: Approximately 14 million cases were analyzed, with almost one-third of them occurring during the pandemic. There was a reduction in the median of the monthly number of emergency department visits in Brazil (-16.5%; p<0.031). Attendances for toothache reduced from a monthly median of 448,802.0 to 377,941.5 (IQR before [IQRa]: 416,291.7-506,150.5; IQR during [IQRd]: 310,251.0-454,206.5), dentoalveolar abscess attendances reduced from 34,929.0 to 27,705.5 (IQRa: 30,215.0-37,870.5; IQRd: 22,216.0-30,048.2) and to dentoalveolar trauma from 16,330.5 to 10,975.0 (IQRa: 14,800.0-18,472.7; IQRd: 8,111.2-13,527.5). Conclusion: Significant reductions were observed in the performance of emergency dental procedures in PHC during the COVID-19 pandemic.